'Just another vial…': a qualitative study to explore the acceptability and feasibility of routine blood-borne virus testing in an emergency department setting in the UK. Issue 4 (1st May 2019) - Cullen, Lucy; Grenfell, Pippa; Rodger, Alison; Orkin, Chloe; Mandal, Sema; Rhodes, Tim
Abstract : Objectives: Increased test uptake for HIV and viral hepatitis is fast becoming a health priority at both national and global levels. Late diagnosis of these infections remains a critical public health concern in the UK. Recommendations have been issued to expand blood-borne virus (BBV) testing in alternative settings. Emergency departments (EDs) offer a potentially important point of testing. This paper presents findings from a qualitative study which aimed to explore the acceptability and feasibility of a routine opt-out combined BBV testing intervention implemented at an inner London ED. Methods: We conducted 22 semistructured interviews with patients and service providers in the ED over a 4-month period during the intervention pilot. A grounded analytical approach was employed to conduct thematic analysis of qualitative study data. Results: Core interrelating thematic areas, identified and analytically developed in relation to test intervention implementation and experience, included the following: the remaking of routine test procedure; notions of responsibility in relation to status knowledge and test engagement; the opportunity and constraints of the ED as a site for testing; and the renegotiation of testing cultures within and beyond the clinic space. Conclusion: Study findings demonstrate how relational and spatial dynamics specific to the ED setting shape test meaning and engagement. We found acceptability of the test practice was articulated through narratives of situated responsibility, with the value of the test offset by perceptions of health need and justification of the test expense. Participant accounts indicate that the nontargeted approach of the test affords a productive disruption to 'at-risk' identities, yet they also reveal limits to the test intervention's 'normalising' effect. Evaluation of the intervention must attend to the situated dynamics of the test practice if opportunities of an opt-out BBV test procedure are to be fully realised. Findings also highlight the critical need to further evaluate post-test intervention practices and experiences.